THE COMET ASSAY APPLICATION FOR ESTIMATION OF DNA DAMAGE AND REPAIR. 1. ESTIMATION OF ENDOGENOUS DNA DAMAGE (Proceedings of the YSU B: Chemical and Biological Sciences, 2003)
Comet assay (CA) – single cells gel-electrophoresis can be used for effective estimate of DNA damage induced by endogenous agents. In cells of patients with periodic disease the increase of spontaneous and induced by endonuclease III levels of DNA damage compared with healthy subjects has not been revealed.
Keywords: periodic disease; endonuclease; single cells gel-electrophoresis